Inheritance of seed coat color and heritability of agronomic characters of F2 population of reciprocal crosses between Fore Belu and Local Sabu mungbean varieties - YOSEP SERAN MAU; ANTONIUS S. S. NDIWA; WIDASARI BUNGA; ZAINAL ABIDIN; TITIK S. HARINI; SHIRLY S. OEMATAN; EFFY ROEFAIDA; ARISTARKHUS TALOIM; ADRIANA GADJI; MARIA RISNAWATI; RIGOBERTUS ASA NANA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mau YS, Ndiwa ASS, Bunga W, Abidin Z, Harini TS, Oematan SS, Roefaida E, Taloim A, Gadji A, Risnawati M, Nana RA. 2023. Inheritance of seed coat color and heritability of agronomic characters of F2 population of reciprocal crosses between Fore Belu and Local Sabu mungbean varieties. Biodiversitas 24: 2647-2656. Mungbean (Vigna radiata (L.) R.Wilczek) is an important pulse crop well adapted to the agro-climatic conditions of East Nusa Tenggara Province, Indonesia. However, the productivity of mungbean in East Nusa Tenggara is low (~0.5 t ha-1). Plant breeding programs can overcome this problem by assembling superior varieties. This study aimed to determine the genetic control of seed coat color and heritability of agronomic traits of F2 population of reciprocal crosses between Fore Belu and Local Sabu mungbean varieties. The observed data included seed coat color and agronomic traits. Seed coat color was subjected to chi-square analysis while agronomic traits were subjected to a simple statistical analysis. The results showed that seed coat color was controlled by one co-dominant gene. The plant heights of F2 fell between the two parental means while the number of pods and seed weight fell below the two parental means. The F2 values range was wide and the maximum F2 values were above the parental means. The phenotypic and genetic variability was wide while either the phenotypic diversity or genetic diversity was moderate to high. The heritability values of the six observed traits were high. The highest was observed on the harvesting date (0.92 and 0.94 for reciprocal crosses), whereas the lowest was on seed weight per plant (0.50 and 0.58 for reciprocal crosses).